2016
DOI: 10.1152/ajpcell.00052.2015
|View full text |Cite
|
Sign up to set email alerts
|

Lewis lung carcinoma regulation of mechanical stretch-induced protein synthesis in cultured myotubes

Abstract: Gao S, Carson JA. Lewis lung carcinoma regulation of mechanical stretch-induced protein synthesis in cultured myotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 77 publications
1
56
0
Order By: Relevance
“…8E, treatment with 4‐PBA for 12 h considerably reduced the rate of protein synthesis in cultured myotubes. Studies have shown that the addition of LLC‐CM initially increases protein synthesis, potentially to counter atrophy signals, whereas long‐term (.48 h ) treatment inhibits protein synthesis in myotubes (56). We found a modest up‐regulation in protein synthesis by treatment of myotubes with LLC‐CM.…”
Section: Resultsmentioning
confidence: 99%
“…8E, treatment with 4‐PBA for 12 h considerably reduced the rate of protein synthesis in cultured myotubes. Studies have shown that the addition of LLC‐CM initially increases protein synthesis, potentially to counter atrophy signals, whereas long‐term (.48 h ) treatment inhibits protein synthesis in myotubes (56). We found a modest up‐regulation in protein synthesis by treatment of myotubes with LLC‐CM.…”
Section: Resultsmentioning
confidence: 99%
“…Although mTOR, FOXO and NF-κB have well-described roles in cancer-induced wasting and disuse, the regulation of these pathways and their effectors may differ between conditions [170] . To this end, exercise and stretch can also activate muscle NF-κB signaling [255257] , in addition to activating mTOR by Akt independent signaling [258] . Further research is needed to determine the consequences of simultaneously activating disuse and cachectic signaling pathways in muscle.…”
Section: Cancer Cachexia-induced Regulation Of Skeletal Muscle Oximentioning
confidence: 99%
“…While AMPK activation by systemic IL-6 also corresponds with mTORC1 suppression in tumor-bearing mice [ 94 ], AMPK inhibition could rescue IL-6-induced suppression of mTORC1 signaling in C 2 C 12 myotubes [ 94 ]. Moreover, inhibition of myotube AMPK activity during LLC treatment improved mTORC1 signaling and protein synthesis [ 95 ]. In contrast to the acute effects of exercise on AMPK activity in healthy skeletal muscle, the chronic activation of AMPK by cachexia or IL-6 overexpression is uncoupled from mitochondrial biogenesis [ 11 , 97 ].…”
Section: Muscle Oxidative Metabolism Regulation Of Protein Synthesmentioning
confidence: 99%
“…While the mechanisms associated with feeding-induced protein synthesis during cancer are starting to emerge, much less is known related to the acute anabolic response to contraction in cachectic muscle. We have reported that mechanoactivation of protein synthesis in stretched myotubes is disrupted by conditioned media from Lewis lung carcinoma (LLC) cells [ 95 ], suggesting that tumor-derived cachectic factors can interfere with mechanical signaling inducing protein synthesis in vitro . In addition, we found that severe cachexia could disrupt the metabolic and anabolic signaling response to a single bout of stimulated concentric muscle contractions [ 110 ].…”
Section: Cancer-induced Anabolic Resistancementioning
confidence: 99%